Analysis Of Stall Rental Practices in Terms of Islamic Economics (Study at Panorama Market Bengkulu City) - -, Diah Sri Yuningsih; Mursalin, Supardi; Cahyono, Andi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This research aims to find out how the practice of renting stalls is in the Panorama Market, Bengkulu City in terms of Islamic economics. This type of research is field research with a descriptive qualitative approach. The research object is the Panorama Market, Bengkulu City. Research data collection techniques using observation, interviews and documentation. The data analysis technique for this research is descriptive qualitative. Qualitative research process is carried out using deductive techniques. The results of the research found that the practice of renting stalls at the Panorama market in Bengkulu City, the use of stalls as objects of use by traders for selling. Processing of stall benefits is only carried out on a lease basis between Panorama Market UPTD and traders. The rental agreement is made verbally. The stall rental fee is charged to the trader or stall renter in the amount of IDR 23. 000 per month rental payments are made every month and will be taken directly by the Panorama Market UPTD. Implementing the agreement, as many as 70% of traders or stall renters neglected to pay rental fees, payments were made negligently, not according to the promised due date and were made continuously. so that it is detrimental to Panorama Market UPTD. There is injustice in fulfilling the rental payment agreement, because they do not carry out the rental payment agreement honestly (sidiq) and responsibly (amanah). Economic actors are not allowed to pursue personal gain if it harms other people